2017
DOI: 10.1002/adfm.201703967
|View full text |Cite
|
Sign up to set email alerts
|

Traceable Nanoparticles with Spatiotemporally Controlled Release Ability for Synergistic Glioblastoma Multiforme Treatment

Abstract: Doxorubicin (DOX), one of the most widely used clinical antineoplastics, has ineffective therapeutic efficacy on glioblastoma multiforme (GBM) with extremely short survival time due to many obstacles such as blood-brain barrier (BBB), tumor angiogenesis, and glioblastoma stem cells (GSCs). To overcome, biocompatible nanoparticles named CARD-B6 loading three clinical drugs are developed. Unlike other nanomedicines, CARD-B6, with the ability of spatiotemporally controlled release, maximize the effectiveness of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…Of the 24 articles identified in the Cochrane Library, no articles were included, as 16 articles were reviews, 5 were protocols, and 3 were clinical articles in the screening analysis. In total, only 27 full-text articles not duplicated were included in this systematic review [ 32 , 34 , 38 , 41 , 43 , 44 , 45 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 24 articles identified in the Cochrane Library, no articles were included, as 16 articles were reviews, 5 were protocols, and 3 were clinical articles in the screening analysis. In total, only 27 full-text articles not duplicated were included in this systematic review [ 32 , 34 , 38 , 41 , 43 , 44 , 45 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The major tumoral cell characteristics used in the selected studies in our review are shown in Table 1 . Of 27 selected studies for this review, 19 studies (70%) [ 32 , 34 , 38 , 43 , 45 , 48 , 52 , 53 , 55 , 56 , 57 , 58 , 59 , 62 , 63 , 64 , 65 , 66 , 67 ] used tumor cells from a human source, 6 (22%) [ 41 , 51 , 54 , 60 , 61 , 68 ] used tumor cell from rats, and 3 studies (11%) [ 44 , 50 , 66 ] used cells from mice. The study by Agemy [ 66 ] used human and mice tumor cell sources and also used lentivirus H-RasV12-shp53 to induce glioma cells.…”
Section: Resultsmentioning
confidence: 99%
“…For the treatment of glioblastoma (GBM), Lu and colleagues constructed DSPE-PEG 2000 nanoparticles decorated with CARD-B6 peptide and loaded them with three different drugs, ATRA, DOX and Combretastatin A4 (CA4) [178]. B6 is a peptide with high affinity for transferrin receptors, thus allowing the entry of the DDS into the brain through the blood-brain barrier.…”
Section: Stimuli-responsivenessmentioning
confidence: 99%
“…Therefore, hypoxia‐responsive materials have recently attracted increasing attention for use in building imaging probes and drug delivery systems. Lu and coworkers reported a hypoxia‐/pH‐responsive and traceable co‐delivery system for glioblastoma multiforme (GBM) therapy and MRI . This multifunctional co‐delivery system was constructed by assembling SPIONs, targeted ligand B6‐decorated DSPE‐PEG2000, hypoxia‐/pH‐responsive PAE‐amido(A)‐AZO‐ATRA and pH‐responsive PAE‐A‐DOX.…”
Section: Stimuli‐responsive Mnp‐based Drug Delivery Systems For Biomementioning
confidence: 99%